Technological Prospecting and Patents of Nutricional Yeast - Evangelista, Natasha Cecchi (2019)
Nutritional yeast has been emerging as an alternative to traditional dietary supplements, because it has a high concentration of proteins, amino acids, and B-complex vitamins and can be consumed by those with restrictive diets, such as vegetarians and lactose intolerant. The present work aimed at the technological prospection, analysis and understanding of the scope and characteristics of patents related to nutritional yeast, through INPI, Espacenet and USPTO databases, using the Microsoft Excel software, and the methodology proposed by Bahruth et al., which divides prospecting into four distinct phases - preparatory; pre-prospective; prospective and post-prospective. The search process involved the manual refinement of the 227 patents found, so that those that did not fit as nutritional yeasts were excluded. The results obtained of only 64 deposits and 2 patent concessions related to nutritional yeasts – which were searched in the databases between 1925 and June of 2018 - show that the world market still invests little in this type of product. Therefore this area is not yet saturated, with the possibility of being exploited and receiving investments.